Validacija NIR spektroskopije za določanje kakovosti lesnih peletov - Stare, Darja (Les (Ljubljana), 2026)
The use of wood biomass, especially wood pellets, has increased in the EU over the past decade, emphasizing the importance of reliable quality control. The aim of this study was to evaluate the suitability of near-infrared (NIR) spectroscopy as a rapid method for determining pellet quality, in comparison with laboratory methods according to SIST EN ISO standards. Fourteen samples of A1 quality pellets were analysed using both methods, and the moisture content, ash content, bulk density, and mechanical durability were compared. The results were statistically evaluated for agreement and repeatability. The findings show that NIR spectroscopy enables rapid and efficient prediction of some key parameters like moisture and ash content, with good comparability to standard laboratory methods, although it remains limited in determining mechanical properties. From a practical perspective, it is therefore suitable as a tool for rapid assessment of certain parameters like bulk density, and mechanical durability. However, reference laboratory methods remain essential for determining compliance with standards and certification.
Keywords: bližnja rdeča spektroskopija; kakovost; lesna biomasa; near-infrared spectroscopy; NIR; peleti; pellets; quality; wood biomass